Activation of Learning Ethnology by Facilities of Ukrainian Literature - Bartashuk, Olesya (Pedagogical Discourse, 2013)
The possibilities of the use of intersubject connections at the studying of ethnology in the system of professional preparation of philologists-Ukrainians are analysed in the article. In particular, the attention is concentrated on illumination of theoretical and practical aspects of activation of studying of separate themes from the ethnology of Ukraine at the use of artistic compositions from the course of Ukrainian literature. The importance of intersubject connections of ethnology and Ukrainian literature in forming ethnocultural, policultural and professional competence of personality of the future Ukrainian philologist is grounded.